Study on prevention of hypercapnia by nasal high flow in patients undergoing endoscopic retrograde cholangiopancreatography during intravenous anesthesia. Issue 19 (May 2020) - Ayuse, Takao; Sawase, Hironori; Ozawa, Eisuke; Nagata, Kazuyoshi; Komatsu, Naohiro; Sanuki, Takuro; Kurata, Shinji; Mishima, Gaku; Hosogaya, Naoki; Nakashima, Sawako; Pinkham, Max; Tatkov, Stanislav; et al.
Abstract: Background: For relatively invasive upper gastrointestinal endoscopy procedures, such as an endoscopic retrograde cholangiopancreatography (ERCP), and also lower gastrointestinal endoscopy procedures, intravenous anesthesia is routinely used to reduce patient anxiety. However, with the use of intravenous anesthesia, even at mild to moderate depth of anesthesia, there is always a risk of upper airway obstruction due to a relaxation of the upper airway muscles. With the advent of nasal high flow (NHF) devices that allow humidified high flow air through the nasal cavity, can be used as a respiratory management method in the context of anesthesia. AIRVO is commonly used for patients with obstructive sleep apnea and other respiratory disorders. This device uses a mild positive pressure load (several cmH2 O) that improves carbon dioxide (CO2 ) washout and reduces rebreathing to improve respiratory function and therefore is widely used to prevent hypoxemia and hypercapnia. This study aims to maintain upper airway patency by applying NHF with air (AIRVO) as a respiratory management method during intravenous anesthesia for patients undergoing an ERCP. In addition, this study investigates whether the use of an NHF device in this context can prevent intraoperative hypercapnia and hypoxemia. Methods/design: This study design employed 2 groups of subjects. Both received intravenous anesthesia while undergoing an ERCP, and 1 group also used a concurrent nasal cannula NHF device. Here we examine if the use of an NHF device during intravenous anesthesia can prevent hypoxemia and hypercapnia, which could translate to improved anesthesia management. Efficacy endpoints were assessed using a transcutaneous CO2 monitor (TCM). This device measured the changes in CO2 concentration during treatment. Transcutaneous CO2 (PtcCO2) concentrations of 60 mm Hg or more (PaCO2  > 55 mm Hg) were considered marked hypercapnia. PtcCO2 concentrations of 50 to 60 mm Hg or more (equivalent to PaCO2  > 45 mm Hg) were considered moderate hypercapnia. Furthermore, the incidence of hypoxemia with a transcutaneous oxygen saturation value of 90% or less, and whether the use of NHF was effective in preventing this adverse clinical event were evaluated. Discussion: The purpose of this study was to obtain evidence for the utility of NHF as a potential therapeutic device for patients undergoing an ERCP under sedation, assessed by determining if the incidence rates of hypercapnia and hypoxemia decreased in the NHF device group, compared to the control group that did not use this device. Trial registration: The study was registered in the jRCTs 072190021. URL https://jrct.niph.go.jp/en-latest-detail/jRCTs072190021 .